Solid-State Fermentation With Aspergillus cristatus Enhances the Protopanaxadiol- and Protopanaxatriol-Associated Skin Anti-aging Activity of Panax notoginseng - Sunmin Lee; Sunmin Lee; Chagam Koteswara Reddy; Jeoung Jin Ryu; Seoyeon Kyung; Yonghwan Lim; Myeong Sam Park; Seunghyun Kang; Choong Hwan Lee (Frontiers in Microbiology, 2021)
A metabolomics approach was used to profile metabolites of Panax notoginseng fermented with Aspergillus cristatus in two ways, liquid-state fermentation (LF-P) and solid-state fermentation (SSF-P) and examine metabolite markers representing antioxidant activity and skin anti-aging. Protopanaxadiol (PPD) and protopanaxatriol (PPT) contents were higher in SSF-P than in LF-P and showed a multiplicative increase over the fermentation period of four days. PPD and PPT levels also correlated with antioxidant and anti-aging effects in skin, based on the mRNA expression of dermal extracellular matrix components. In the bioactivity validation assays, PPD and PPT significantly improved the expression of type-I collagen, fibrillin-1, and elastin in human dermal fibroblasts from both young and old subjects; these were comparable with the effects of the SSF-P extracts. Overall, our results suggest that changes in the metabolites of P. notoginseng fermented with A. cristatus enhance the quality and availability of bioactive compounds associated with skin anti-aging.